AKUNTABILITAS KEUANGAN DESA (STUDI KASUS DESA NGENTRONG KECAMATAN KARANGAN KABUPATEN NGANJUK) - Hanum, Fauziah (Universitas Kadiri, 2019)
This study analyzes the accountability of village funds and the key factors. This study uses a qualitative approach by conducting in-depth interviews with informants at every stage of planning, implementing, administering, reporting, accountability, coaching, and supervision of village financial management. The results of this study indicate that village financial accountability is applied by law number 6 of 2014 with the critical factors of the effectiveness of the village government in managing finances independently but is accompanied by a less than the optimal role of the village consultative body (BPD).